2003
DOI: 10.1093/annonc/mdg367
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ibandronate reduces the incidence of skeletal complications in patients with breast cancer and bone metastases

Abstract: These results indicate that 6 mg i.v. ibandronate is effective and safe in the treatment of bone metastases from breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(89 citation statements)
references
References 20 publications
3
82
0
4
Order By: Relevance
“…The results for fractures did not reach statistical significance in contrast to the data for i.v. ibandronate (Body et al, 2003a), and the patients had overall less fractures in the oral studies. Since a large meta-analysis of clinical trials has shown that bisphosphonates significantly decrease skeletal morbidity including fractures and need for radiotherapy (Ross et al, 2003), the trend that was observed for oral ibandronate will need to be confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The results for fractures did not reach statistical significance in contrast to the data for i.v. ibandronate (Body et al, 2003a), and the patients had overall less fractures in the oral studies. Since a large meta-analysis of clinical trials has shown that bisphosphonates significantly decrease skeletal morbidity including fractures and need for radiotherapy (Ross et al, 2003), the trend that was observed for oral ibandronate will need to be confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 81%
“…As demonstrated for i.v. ibandronate (Body et al, 2003a;Lyubimova et al, 2003), oral ibandronate was not associated with renal AEs. This contrasts with the enhanced risk of renal AEs reported with i.v.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Of these 31 studies, 6 reported on bone metastases from breast cancer, [71][72][73][74][75][76] 13 reported on bone metastases from prostate cancer [77][78][79][80][81][82][83][84][85][86][87][88][89] and 12 reported on bone metastases from OSTs. [90][91][92][93][94][95][96][97][98][99][100][101] Of the remaining eight studies that did contribute data to the network meta-analyses, four reported breast cancer 31,[102][103][104] [18 reports 22,31,[102][103][104][105][106][107][108][109][110][111][112][113][11...…”
Section: Number and Type Of Studies Includedmentioning
confidence: 99%
“…There have been no published reports of ibandronate-related renal failure in this indication [29]. Intravenous ibandronate (6 mg infused every 3–4 weeks) has also been shown to be effective and well tolerated as a treatment for hypercalcemia and other complications of malignant bone disease, such as fractures and bone pain [12, 30, 31]. …”
Section: Introductionmentioning
confidence: 99%